Carcinosarcoma: a rare sinonasal malignancy with atypical behaviour - Miranda, Vera; Soares Santos , Tiago; Gonçalves, Paulo; Pestana Aguiar , Catarina; Gonçalves, Débora; Lopes, Miguel Campos; Carvalho, Carlos (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Carcinosarcoma is an extremely rare neoplasm in the nasal cavity and in the paranasal sinus, with rapid growth and extensive local destruction. We report a case of a 61-year-old man with progressive left-side nasal obstruction and epiphora for six months. Imaging showed a massive mass lesion, mainly located in the left nasal cavity and ethmoid sinus, with no intracranial or orbital extension. Biopsy of the nasal mass revealed a poorly-differentiated squamous cell carcinoma associated with sarcomatous elements. Patient underwent an endoscopic transnasal resection. Definitive histopathologic analysis revealed a carcinosarcoma. Postoperative radiotherapy was, then, performed. After five years of follow-up, there is no evidence of tumor recurrence. This report highlights that even though despite the lack of optimal treatment protocol, long term disease control can be achieved through endoscopic transnasal resection complemented with radiotherapy.